3(4x-7)(4x+3)=0

Simple and best practice solution for 3(4x-7)(4x+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x-7)(4x+3)=0 equation:

3(4x-7)(4x+3)=0
We multiply parentheses ..
3(+16x^2+12x-28x-21)=0
We multiply parentheses
48x^2+36x-84x-63=0
We add all the numbers together, and all the variables
48x^2-48x-63=0
a = 48; b = -48; c = -63;Δ = b2-4acΔ = -482-4·48·(-63)Δ = 14400The delta value is higher than zero, so the equation has two solutionsWe use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{14400}=120$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-48)-120}{2*48}=\frac{-72}{96} =-3/4$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-48)+120}{2*48}=\frac{168}{96} =1+3/4$

`